Primary Diffuse Leptomeningeal Gliomatosis: Radiological/Pathological Features - Ehtasham Ahmad; Mohamed Mohamed; Apostolos Vrettos (Case Reports in Neurological Medicine)
We present the case of a 43-year-old lady who presented with headaches, visual impairment, and seizures, progressing rapidly over the course of a few weeks. Extensive workup excluded an inflammatory or infectious cause. Imaging studies revealed diffuse thickening of the leptomeninges and serial CSF analysis showed raised opening pressures and increased protein levels. A diagnostic biopsy of the lower thoracic dura confirmed the diagnosis of primary diffuse leptomeningeal gliomatosis (PDGL). She was managed supportively for her symptoms and unfortunately she passed away a few weeks later.